Physical Activity, Screen Time and Subjective Well-Being Among Children [Actividad Física, Tiempo Frente a la Pantalla y Bienestar Subjetivo en Niños] - Fernandez-Vergara, O; Garcia-Hermoso, A; Hormazabal-Aguayo, I (Elsevier Doyma, 2020)
Background/Objective: The aim of the study was to explore the differences between physical activity and/or screen time levels on cognitive (Life satisfaction LS) and affective (Positive affect, PA and Negative affect NA) components of subjective well-being (SWB) in children. Method: This cross-sectional study enrolled 1,540 children (1,040 boys, 8–12 years old). LS, PA, NA, physical activity and screen time were assessed with validated questionnaires. Results: Children who reported 3 days per week of physical activity or less had lower LS and PA than counterparts with ≥6 days of physical activity per week (p < .05). Participants who reported 2 hours per day or less of screen time had lower NA than counterparts with 4 hours per day or more of screen time (p < .05). Also, children who meet physical activity guidelines have higher LS and PA compared to inactive peers, even with high screen time. In contrast, excessive screen time was also related with NA independent of the level of physical activity. Conclusions: Our findings suggest that physical activity is related with positive feelings and LS, but does not eliminate the effect of screen time on negative feelings among Chilean children. © 2020 Asociación Española de Psicología Conductual